A novel approach for high-yield solid few-layer MoS2 nanosheets with effective photocatalytic hydrogen evolution. (21st June 2019) - Wan, Jun; Wang, Ruimiao; Liu, Lin; Fan, Jun; Liu, Enzhou; Gao, Xiaoming; Fu, Feng
Abstract: Few-layer molybdenum disulfide (MoS2 ) nanosheets are well applied in many field, but the lack of simple methods for the preparation of solid few-layer MoS2 nanosheets with high yield and quality has greatly restricted their development. In this work, a facile solvothermal treatment coupled with the liquid exfoliation strategy was conducted to produce solid monodispersed few-layer MoS2 nanosheets from the MoS2 stack, and the output can reach as high as approximately 0.3 g/g. The few-layer features were confirmed by characterizations of SEM, TEM, Raman spectra, UV–vis absorption spectrum and PL spectrum. The obtained MoS2 nanosheets exhibit fantastic dispersity and stability in an NMP solution, which can remain uniform even after one year. In general, pure MoS2 catalysts show no or poor activity for photocatalytic hydrogen evolution as reported in the literature, however, the prepared MoS2 nanosheets in this work display excellent photocatalytic H2 evolution performance of 1241.3 μmol g −1 h −1 due to the synergistic structural and electronic modifications, including a bigger specific surface area, additional exposed active edge sites, superior charge separation and transfer efficiency, and higher reduction potential. Highlights: A simple synthesized method of solid few-layer MoS2 nanosheets was developed. The output of few-layer MoS2 nanosheets can reach as high as approximately 0.3 g/g. The obtained MoS2 nanosheets exhibit fantastic dispersity and stability in solution. The prepared MoS2 nanosheets display excellent photocatalytic H2 evolution performance.